ANALISIS KEPENTINGAN SPECIAL SAFEGUARD MECHANISM INDONESIA DALAM NEGOSIASI PERTANIAN DI WORLD TRADE ORGANIZATION (WTO) - Adrian Darmawan Lubis; Firman Mutakin; Reni K. Arianti (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Multilateral liberalization negotiations at the World Trade Organization is currently discussing the issue of protecting domestic producers from import surge through the scheme of Special Safeguard Mechanism (SSM). SSM negotiations currently discussing the method of determining the value of SSM trigger. The results of this study found that the three-month Moving Average Method-by not using pro-rating-is the best method of determining SSM trigger value for Indonesia. However, data limitations led Indonesia to only be able to monitor changes in price for 5.67% of total agricultural products are traded. Therefore, it is necessary to establish institutions that are authorized to analyze the impact of changes in prices and imports, where the results will be used as a determinant when the SSM is implemented.